Non-covalent intermolecular interactions of colloidal nematic liquid crystals doped with graphene oxide. Issue 9 (15th July 2017) - Javadian, Soheila; Dalir, Nima; Kakemam, Jamal
ABSTRACT: Graphene oxide (GO) was doped to eutectic uniaxial nematic liquid crystals (NLCs) (E5CN7 ) with different percentages to improve the physiochemical properties of NLCs effectively. GO shifts the N-I phase transition temperature to higher values. It has been observed that increasing GO concentration up to 0.75% increases the N-I phase transition temperature substantially while further increase of GO concentration results in an inverse trend. The GO/E5CN7 non-covalent interactions change the N-I phase transition. The contribution of several terms such as anchoring and polarisation effects on N-I phase transition was quantified as well. The results suggest that the size is an important contributor to GO and liquid crystal interaction. The results show that E5CN7 @GO composites may act as promising candidates to enhance the efficiency of room temperature devices. GRAPHICAL ABSTRACT: